Norwegian media substantiation of counterterrorism measures. Issue 1 (2nd January 2016) - Jore, Sissel H.
Abstract : The aim of this article is to investigate how terrorism countermeasures have been justified and reasoned for in the public arena, specifically in Norwegian media discourses from 1993 to 2007. Changes in the media discourse on the terrorism threat and terrorism countermeasures have been investigated by analyzing the changes in the media representation of the terrorism threat and the arguments behind the implementation of counterterrorism measures. The analysis shows that the media's framing of terrorism has gone from presenting terrorism mainly as a threat against specific people or delimited events related to international conflicts in the 1990s to a threat against civilians and whole sectors of society after 9/11. Terrorism is presented through the media after 9/11 as an omnipresent, societal threat that citizens should be protected from no matter how low the probability of this terrorism might be. In parallel, counterterrorism measures have gone from being described as threats against civil liberties in the 1990s to a necessity after 9/11. The media articles have given a picture of terrorism countermeasures as a topic not defined on the basis of traditional normative risk criteria. As presented in the media, these measures seem beyond rational evaluation and assessment. They have primarily been described as necessary and independent of the risk; factors such as precaution, compliance, solidarity, and moral obligations have been the dominant underpinning arguments behind their implementation. This approach to counterterrorism might (if unquestioned) pave the way for further implementation of such measures.